2007
DOI: 10.1016/j.jim.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of the CD107 mobilization assay reveals that cytotoxic T lymphocytes with novel MHC-Ib restriction are activated during Listeria monocytogenes infection

Abstract: Detection of cytotoxic activity by pathogen-specific T cells of unknown antigenic specificity is difficult due to the limitations of using infected cells, instead of peptide-pulsed cells, as targets. We report here that the recently described CD107 mobilization assay readily allowed for the ex vivo detection of cytotoxic T lymphocytes (CTL) with a novel MHC-Ib restriction that specifically recognized Listeria monocytogenes-infected macrophages. The CD107 mobilization assay is likely to be a useful tool for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Purified human monocytes from mycobacterial purified protein derivative (PPD)‐responder healthy individuals were infected with B. abortus in the presence of IFN‐γ, pulsed with Mycobacterium tuberculosis lysate and incubated with autologous purified CD8 + T cells. Macrophages treated with IFN‐γ alone presented MHC‐I‐restricted epitopes recognized by autologous PPD‐specific purified CD8 + T cells as evidenced by the ability of these cells to upregulate the CD8 + activation marker CD107a (McElroy et al ., ) and to produce IFN‐γ when compared with untreated cells (Fig. A and B).…”
Section: Resultsmentioning
confidence: 93%
“…Purified human monocytes from mycobacterial purified protein derivative (PPD)‐responder healthy individuals were infected with B. abortus in the presence of IFN‐γ, pulsed with Mycobacterium tuberculosis lysate and incubated with autologous purified CD8 + T cells. Macrophages treated with IFN‐γ alone presented MHC‐I‐restricted epitopes recognized by autologous PPD‐specific purified CD8 + T cells as evidenced by the ability of these cells to upregulate the CD8 + activation marker CD107a (McElroy et al ., ) and to produce IFN‐γ when compared with untreated cells (Fig. A and B).…”
Section: Resultsmentioning
confidence: 93%
“…No pre-incubation with brefeldin A or monensin was used prior to intracellular staining. For CD107a mobilization assay, cells were cultured in the presence of monensin (1 μM, Sigma) and anti-CD107a (4 μL/ml, Biolegend) for 4 h using a modified version of a previously described method (McElroy et al, 2007). Additionally, cells were cultured with or without ionomycin (250ng/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the presence of CD107a + correlates well with cytotoxic activity of CD8 + T cells. 26 Following incubation of P815 cells with anti-CD3 mAb, we coated the cells with or without the FN726 and its Fap2 mutant FNK50, and then co-cultured the P815 cells with CEACAM1 + CD8+ T cells, and stained the CD8 + T cells for CD107a.…”
Section: F Nucleatum Inhibits T Cells and Nk Cells Functionmentioning
confidence: 99%